THE STUDY OF OBSTETRIC OUTCOME IN TEENAGE PRIMIGRAVIDAE - J.V.KULKARNI; V.G.KULKARNI; SREEKANTHA; AVINASH S S (International Journal of Pharma and Bio Sciences, 2014)
Teenage pregnancy is a fairly common occurrence in India, due to many factors such as early marriages, illiteracy,ignorance,social and religious factors.The changes in the attitude of the general population towards sex, the impact of media television, movies and literature, which are sex-oriented, are responsible for present adolescent behavior.The adolescent above the age of 15, who escapes toxaemia, anaemia and premature labour seems to enjoy a relatively benign obstetric course. In conclusion, pregnant teenagers are definitely at greater risk, requiring additional efforts and resources to serve and project their total health. They need more attention for prevention and treatment of preeclamspia, eclampsia, anaemia and last but not the least, prematurity and low birth-weight.This study deals with etiology,etipathogenesis,health education and preventive aspects of shortening mortality of teenage mothers and baby.